Supporting English Public Speaking Development: A Community Service Activity in Speech Judging - Ummi Qalsum Arif (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Public speaking is a crucial skill in English language learning, particularly in English as a Foreign Language (EFL) contexts. However, many learners face challenges such as anxiety, limited exposure, and lack of structured practice. This study reports a community service activity aimed at improving English public speaking skills through speech judging training for Senior High School level. The program involves workshops, simulations, and evaluative practices. Using a mixed methods approach, data were collected through observation, performance assessment, and participant feedback. The findings reveal that integrating speech judging into training significantly enhances learners’ fluency, confidence, and critical thinking. The study suggests that community based programs can provide effective platforms for developing communicative competence in EFL